Scutum reconstruction technique and classification in endoscopic middle ear cholesteatoma surgery. (1st November 2020) - Wu, Nan; Zuo, Wenjing; Wang, Fangyuan; Hou, Kun; Yang, Shiming; Hou, Zhaohui
Abstract: Background: Endoscopy has been increasingly used in middle ear cholesteatoma surgery. It can increase the proportion of canal wall up (CWU) surgery and effectively control the recurrence and residual rates. However, there is a lack of systematic description on scutum reconstruction technique in endoscopic middle ear cholesteatoma surgery. Objective: The technique and classification of scutum reconstruction in endoscopic cholesteatoma surgery were proposed, and the outcomes were preliminarily evaluated. Methods: According to the development of mastoid and the way of hearing reconstruction, the reconstruction of scutum was classified into three types. The rates of residual and recurrence and hearing outcomes were observed and analyzed. Results: A total of 57 patients underwent endoscopic cholesteatoma surgery, all of which were CWU surgery. The reconstruction of the scutum was performed using tragal cartilage according to three types. The residual of cholesteatoma was observed in three cases. The recurrence of cholesteatoma and retraction pocket was detected in two cases and five cases, respectively. Postoperative hearing results were generally satisfied in all three types of surgeries. Conclusion: The technique of scutum reconstruction in endoscopic cholesteatoma surgery in this work can effectively control the recurrent disease after CWU surgery.